A Comparative Study of Some Values of ionization constants of Oximes and Phenolic Acids Derived fromِ Aliphatic and Aromatic Carbonyl Compounds - Adil Azooz; Maathir Al-Zubaidy (College of Education for Pure Sciences, 1999)
Abstract The project includes on the determination of ionization constants kn for thirteen acidic new imines as derived form aliphatic and aromatic ketones with different aldehydes, where n is the number of acid. These acids contain acid groups in a forms of oxime, phenol or their mixture. The study led to a comparison of ionization constants for the acidic similar compounds in a forms of oximes and phenols. A simple, rapid and precise conductivity method is used for the determination of ionization constants for acids. Generally, the values of ionization constants for acids under study are found to depend mainly on the following factors:- The structure of acid, the ambient temperature and the nature of inter or intra molecular hydrogen bonding in acids under study.